Mechanistic influence of the torque cadence relationship on power output during exhaustive all-out field tests in professional cyclists - Leo, P.; Martinez-Gonzalez, B.; Mujika, I.; Giorgi, A. (Journal of Sports Sciences, 2025)
Understanding the torque-cadence-power relationship can be important in assessing a cyclist`s performance potential. This study explored these relationships in elite male cyclists (N = 17; age: 24.1 ± 3.8 years; body mass: 66.0 ± 4.8 kg, critical power (CP): 5.5 ± 0.3 W.kg-1) through sprint, torque, and CP tests conducted in fresh and after accumulated work. Testing protocols, performed during a pre-season training camp, included maximal efforts across varied gear ratios and durations (15 s, 3 min, and 12 min), under stable environmental conditions (15-20°C). Results revealed reduced power output, torque, and cadence after accumulated work compared to fresh conditions (p = .001). Sprint-derived maximum torque (Tmax) was strongly correlated with torque intercepts for CP fresh (r = .558, p = .020) and after accumulated work (r = .556, p = .020). The cadence relationships demonstrated a large negative correlation between maximum cadence (Cmax) and optimum cadence (Copt) from the sprint test and the 15 s, 3 min and 12 min cadence recorded during CP after accumulated work (r = -0.541 to -0.634, p = 0.006 to 0.025). These findings highlight that accumulated work-induced reductions in work capacity (W`) and CP values were accompanied by lower cadences across all effort durations.